Inter-arm difference of systolic blood pressure measured by automated double-cuff device is associated with arterial stiffness in patients with hypertension. Issue 1 (February 2020) - Iida, Masato; Ishiguro, Yuko; Ueda, Norihiro; Honjo, Haruo
Abstract : Purpose: Inter-arm differences of SBP ≧5 mmHg have been associated with all-cause and cardiovascular mortalities in hypertensive subjects. Inter-arm differences of SBP appears to be mediated by arterial stiffness. We hypothesized inter-arm differences of SBP ≧5 mmHg may be related to higher pulse pressure/stroke volume index, a surrogate marker of arterial stiffness. Materials and methods: To obtain inter-arm differences of SBP (the absolute difference of right and left arm) and ankle-brachial index, bilateral blood pressures were measured simultaneously at the four limbs using an automated oscillometric device in patients with treated hypertension (n = 234) and in normotensive subjects (n = 40). Pulse pressure was calculated as SBP–DBP. Stroke volume was obtained by time-velocity integral method using echocardiography. Left ventricular mass and relative wall thickness were calculated by the conventional methods. Results: All hypertensive patients were medically treated and had average blood pressure levels of 135/85 mmHg. Inter-arm differences of SBP ≧5 mmHg was detected in 26.5% of hypertensive patients. Hypertensive patients with inter-arm differences of SBP ≧5 mmHg had higher pulse pressure/stroke volume index, lower ankle-brachial index, higher BMI, and higher relative wall thickness, higher prevalence of female than those with inter-arm differences of SBP <5 mmHg. Multiple linear regression analysis confirmed inter-arm differences of SBP ≧5 mmHg was associated with higher pulse pressure/stroke volume index, higher relative wall thickness, and lower ankle-brachial index. Conclusion: Inter-arm difference of SBP measured by automated double-cuff device was related to large artery stiffness in patients with hypertension.